Reducing sputter induced stress and damage for efficient perovskite/silicon tandem solar cells. Issue 3 (23rd December 2021) - Liu, Kong; Chen, Bo; Yu, Zhengshan J.; Wu, Yulin; Huang, Zhitao; Jia, Xiaohao; Li, Chao; Spronk, Derrek; Wang, Zhijie; Wang, Zhanguo; Qu, Shengchun; Holman, Zachary C.; et al.
Abstract : The mechanisms of sputter induced stress and damage in perovskite/silicon tandem solar cells were investigated for optimizing buffer layer materials and transparent conductive oxides. A high power conversion efficiency of 26.0% has been achieved. Abstract : Reducing damage caused by sputtering of transparent conductive oxide (TCO) electrodes is critical in achieving highly efficient and stable perovskite/silicon tandem solar cells. Here we study the sputter caused damage to bathocuproine (BCP), which is widely used in highly efficient p–i–n structure single junction perovskite solar cells. While the BCP buffer layer protects the underlying layers from damage, it itself can be damaged by sputtering of TCOs at a wide range of target–substrate distances, supported by molecular dynamics simulation. More intriguingly, it is observed that TCO easily peeled off after sputtering when the sputtering target is close to the substrate. This is ascribed to the formation of stress during the cooling down process after sputtering due to different thermal expansion coefficients of the layers. Our studies explain why tin oxide (SnO2 ) made by atomic layer deposition can replace BCP for a much better tandem device performance. SnO2 has high affinity with the sputtered TCO electrode to suppress the peeling-off issue and has higher bond energy to resist sputter induced damage, thus allowing a wider window of target–substrate distances than BCP during TCO sputtering. Ultimately, we demonstrate an efficient perovskite/silicon monolithic tandem solar cell with an efficiency of 26.0% to illustrate the beneficial effects of reduced stress and damage.